The relationship between pain duration characteristics and pain intensity in herpes zoster-related pain: a single-center retrospective study - Wang, Liu; Lan, Xiaoxiao; Lan, Zhixuan; Xu, Shengrong; He, Ruilin; Jiang, Zongbin (Frontiers in Medicine, 2024)
Background The varicella-zoster virus (VZV) can cause herpes zoster (HZ), which may progress to postherpetic neuralgia (PHN), leading to severe inflammatory responses and pain. Objective This study investigates the relationship between pain duration characteristics and pain intensity in patients with herpes zoster-related pain, hypothesizing that persistent pain correlates with higher pain intensity compared to intermittent pain. Methods A retrospective study was conducted at the Second Affiliated Hospital of Guangxi Medical University, China. Data from patients treated for herpes zoster-related pain between January 2019 and February 2024 were analyzed. Pain intensity was measured using the Numerical Rating Scale (NRS-11), and pain duration was categorized as intermittent or persistent. Multivariate regression models were used to assess the association between pain duration and intensity, adjusting for potential confounders. Results A total of 840 patients were included. Persistent pain was significantly associated with higher NRS-11 scores compared to intermittent pain (β = 0.71, 95% CI 0.50–0.91, p < 0.001). Subgroup analyses showed that persistent pain was associated with higher pain intensity in both acute HZ and PHN patients (HZ: β = 0.71, 95% CI 0.45–0.96, p < 0.001; PHN: β = 0.76, 95% CI 0.40–1.13, p < 0.001). Inflammatory markers, such as C-reactive protein (CRP) and white blood cell count, were positively correlated with pain intensity. Conclusion Pain duration significantly impacts pain intensity in HZ patients. Considering pain duration is crucial for effective pain management. Further research should explore the mechanisms underlying persistent pain to develop better treatment strategies.